Poetics of [Non] Existence: Narratives of the Search for Missing Persons, Comuna 13, Medellín, Colombia - Posada Romero, Luisa Fernanda (2025)
The text presented below is derived from the research Poéticas de la [no] existencia, una aproximación a la lógica del espectro - Comuna 13, Medellín. This study was conducted from an ethnographic perspective, analyzing the narratives of the Mujeres Caminando por la Verdad colective in dialogue with the everyday traces reflected in the representation of their disappeared relatives. The analysis also incorporated theoretical reflections of Derrida (1998, 2000, 2010) and Didi-Huberman (2014). In this sense, the testimonies reveal, in both the self and the absent body, the marks of an event that transformed the ways of being and inhabiting the territory. These women’s narratives become a form of translatability of the experience left by the armed conflict in their community.